Emerging diagnostic markers and therapeutic targets in post-stroke hemorrhagic transformation and brain edema - Yao, Ying; Liu, Fei; Gu, Zhaowen; Wang, Jingyu; Xu, Lintao; Yu, Yue; Cai, Jing; Ren, Reng (Frontiers in Molecular Neuroscience, 2023)
Stroke is a devastating condition that can lead to significant morbidity and mortality. The aftermath of a stroke, particularly hemorrhagic transformation (HT) and brain edema, can significantly impact the prognosis of patients. Early detection and effective management of these complications are crucial for improving outcomes in stroke patients. This review highlights the emerging diagnostic markers and therapeutic targets including claudin, occludin, zonula occluden, s100β, albumin, MMP-9, MMP-2, MMP-12, IL-1β, TNF-α, IL-6, IFN-γ, TGF-β, IL-10, IL-4, IL-13, MCP-1/CCL2, CXCL2, CXCL8, CXCL12, CCL5, CX3CL1, ICAM-1, VCAM-1, P-selectin, E-selectin, PECAM-1/CD31, JAMs, HMGB1, vWF, VEGF, ROS, NAC, and AQP4. The clinical significance and implications of these biomarkers were also discussed.